Dietary Calcium Intake in a Sample of University of San Marcos Students 1998 - Bernui Leo, Ivonne (2001)
OBJECTIVE: To assess the current dietary calcium intake in a sample of Universidad San Marcos students, and the low intake associated health risks. MATERIAL AND METHODS: The current calcium intake in 168 students between the ages 16 and 24 years was measured. The 24 hour recall method and an International-Vitamin-A-Consultative-Group modified semi-quantitative questionnaire which assess calcium usual intake and low intake associated risks along the time were used. RESULTS: The current calcium intake was 557 ± 384 mg Ca+2/d (median 473 mg Ca+2/d). A faulty calcium intake has been found in 86% of the students. There was no difference in calcium intake between genders (p >0,05). People was classified as having a low (0,6%), medium (11%) or high (88%) risk as regards its usual calcium intake. CONCLUSION: In our sample, the calcium intake was below the recommended levels, which could be associated with health disturbances in the years to come.